A novel tropoelastin-based resorbable surgical mesh for pelvic organ prolapse repair. (September 2020) - Aghaei-Ghareh-Bolagh, B.; Mukherjee, S.; Lockley, K.M.; Mithieux, S.M.; Wang, Z.; Emmerson, S.; Darzi, S.; Gargett, C.E.; Weiss, A.S.
Abstract: Pelvic organ prolapse is a common condition that affects 1 in 4 women across all age groups. It is mainly caused by vaginal birth injury and can be exacerbated by obesity and increased age. Until recently, treatment strategies often used non-degradable synthetic meshes for reconstructive surgery. However, owing to their frequent, unacceptable rate of adverse events such as mesh erosion, transvaginal meshes have been banned in many countries. Recent reports have highlighted the urgent need for biocompatible design of meshes for a safe and effective treatment in the long term. This study reports the design and evaluation of a novel, elastin based degradable mesh using an ovine model of POP as a potential surgical treatment. Elastin is a protein component of the ECM and provides elasticity to tissues throughout the body. Tropoelastin, the monomer subunit of elastin, has been used with success in electrospun constructs as it is a naturally cell interactive polymer. Biomaterials that incorporate tropoelastin support cell attachment and proliferation, and have been proven to encourage elastogenesis and angiogenesis in vitro and in vivo . The biological properties of tropoelastin were combined with the physical properties of PCL, a degradable synthetic polymer, with the aim of producing, characterizing and assessing the performance of continuous tropoelastin:PCL electrospun yarns. Using a modified spinneret electrospinning system and adjusting settings based on relative humidity, four blends of tropoelastin:PCL yarns were fabricated with concentration ratios of 75:25, 50:50, 25:75 and 0:100. Yarns were assessed for ease of manufacture, fibrous architecture, protein/polymer content, yarn stability - including initial tropoelastin release, mechanical strength, and ability to support cell growth. Based on overall favorable properties, a mesh woven from the 50:50 tropoelastin:PCL yarn was implanted into the vagina of a parous ewe with vaginal wall weakness as a model of pelvic organ prolapse. This mesh showed excellent integration with new collagen deposition by SEM and a predominant M2 macrophage response with few pro-inflammatory M1 macrophages after 30 days. The woven tropoelastin:PCL electrospun mesh shows potential as an alternative to non-degradable, synthetic pelvic organ prolapse mesh products. Graphical abstract: Image 1